HIV-1 Env induces pexophagy and an oxidative stress leading to uninfected CD4+ T cell death. Issue 9 (2nd September 2021) - Daussy, Coralie F; Galais, Mathilde; Pradel, Baptiste; Robert-Hebmann, Véronique; Sagnier, Sophie; Pattingre, Sophie; Biard-Piechaczyk, Martine; Espert, Lucile
ABSTRACT: The immunodeficiency observed in HIV-1-infected patients is mainly due to uninfected bystander CD4 + T lymphocyte cell death. The viral envelope glycoproteins (Env), expressed at the surface of infected cells, play a key role in this process. Env triggers macroautophagy/autophagy, a process necessary for subsequent apoptosis, and the production of reactive oxygen species (ROS) in bystander CD4 + T cells. Here, we demonstrate that Env-induced oxidative stress is responsible for their death by apoptosis. Moreover, we report that peroxisomes, organelles involved in the control of oxidative stress, are targeted by Env-mediated autophagy. Indeed, we observe a selective autophagy-dependent decrease in the expression of peroxisomal proteins, CAT and PEX14, upon Env exposure; the downregulation of either BECN1 or SQSTM1/p62 restores their expression levels. Fluorescence studies allowed us to conclude that Env-mediated autophagy degrades these entire organelles and specifically the mature ones. Together, our results on Env-induced pexophagy provide new clues on HIV-1-induced immunodeficiency. Abbreviations: Ab: antibodies; AF: auranofin; AP: anti-proteases; ART: antiretroviral therapy; BafA1 : bafilomycin A1 ; BECN1: beclin 1; CAT: catalase; CD4: CD4 molecule; CXCR4: C-X-C motif chemokine receptor 4; DHR123: dihydrorhodamine 123; Env: HIV-1 envelope glycoproteins; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; GFP: green fluorescent protein; GFP-SKL: GFP-serine-lysine-leucine; HEK: human embryonic kidney; HIV-1: type 1 human immunodeficiency virus; HTRF: homogeneous time resolved fluorescence; MAP1LC3/LC3: microtubule associated protein 1 light chain 3; NAC: N-acetyl-cysteine; PARP: poly(ADP-ribose) polymerase; PEX: peroxin; ROS: reactive oxygen species; siRNA: small interfering ribonucleic acid; SQSTM1/p62: sequestosome 1.